Dynamic changes in the gastrointestinal microbial communities of Gangba sheep and analysis of their functions in plant biomass degradation at high altitude - Xiaozhen Liu; He Ding; Xiaoxue Zhang; Na Ta; Jinmei Zhao; Qian Zhang; Huiyun Liu; Mengjiao Sun; Xiaoqing Zhang (Microbiome)
Abstract Background While Gangba sheep being well known for their unique flavour and nutritional value, harsh environmental factors negatively affect their growth and development, leading to poor productivity. The gastrointestinal tract microbiota plays an important role in host nutrient absorption and metabolism. The identification of dynamic changes in the gastrointestinal microbial communities and their functions is an important step towards improving animal production performance and health. Results A comprehensive multi-omics survey of the microbial communities of the Gangba sheep gastrointestinal tract was performed under three distinct feeding strategies: natural grazing, semi-grazing with supplementation, and barn feeding. The dynamic changes, cross-kingdom partnerships and functional potential profiles were analysed and the results revealed that the feeding strategies had a greater impact on the microbial communities than the site of the gastrointestinal tract. The different microbial associations among the groups were revealed by co-occurrence networks based on the amplicon sequence variants (ASVs). Moreover, a Gangba sheep gastrointestinal microbial genomic catalogue was constructed for the first time, including 1146 metagenome-assembled genomes (MAGs) with completeness > 50% and contamination < 10%, among which, 504 bacterial and 15 archaeal MAGs were of high quality with completeness > 80% and contamination < 10%. About 40% of the high-quality MAGs displaying enzyme activity were related to the microbial species that contribute to plant biomass degradation. Most of these enzymes were expressed in rumen metatranscriptome datasets, especially in Prevotella spp. and Ruminococcus spp., suggesting that gastrointestinal microbial communities in ruminants play major roles in the digestion of plant biomass to provide nutrition and energy for the host. Conclusions These findings suggest that feeding strategies are the primary cause of changes in the gastrointestinal microbiome. Diversification of livestock feed might be an effective strategy to maintain the diversity and ecological multifunctionality of microbial communities in the gastrointestinal tract. Additionally, the catalogue of microbial genomes and the encoded biomass-degrading enzymes identified here provide insights into the potential microbial functions of the gastrointestinal tract of Gangba sheep at high altitudes. This paves the way for microbial interventions to improve the growth performance, productivity and product quality of ruminant livestock. Video Abstract